The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s0003-4878(00)00050-8
|View full text |Cite|
|
Sign up to set email alerts
|

Postulating a dermal pathway for exposure to anti-neoplastic drugs among hospital workers. Applying a conceptual model to the results of three workplace surveys

Abstract: Dermal exposure to anti-neoplastic drugs has been suggested as a potentially important route of exposure of hospital workers. Three small-scale workplace surveys were carried out in several hospitals focusing on contamination by leakage from IV infusion systems; contamination by spilled urine of patients treated with anti-neoplastic drugs and particulate phase anti-neoplastic drugs in the air of outpatient and nursing clinics. A new visual scoring technique using a fluorescent tracer was developed. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 19 publications
4
77
0
3
Order By: Relevance
“…Recent studies showed also that antineoplastic levels in air samples were not significantly detected, suggesting that inhalation might have a lower impact when assessing exposure (Mason et al 2005;Connor et al 2010;Huang et al 2012). Therefore, contact with contaminated workplace surfaces without gloves seems to play an important role in the dermal exposure to antineoplastic drugs (Hirst et al 1984;Sessink et al 1994;Kromhout et al 2000;Fransman et al 2005;Schierl et al 2009). In this context, most of the recently published studies give particular attention to the assessment of surfaces contamination and report a generalized contamination, even in hospitals with the best equipment and strict safety procedures (Turci et al 2003;Hedmer et al 2005;Mason et al 2005;Brouwers et al 2007;Hon et al 2011Hon et al , 2013Kopp et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed also that antineoplastic levels in air samples were not significantly detected, suggesting that inhalation might have a lower impact when assessing exposure (Mason et al 2005;Connor et al 2010;Huang et al 2012). Therefore, contact with contaminated workplace surfaces without gloves seems to play an important role in the dermal exposure to antineoplastic drugs (Hirst et al 1984;Sessink et al 1994;Kromhout et al 2000;Fransman et al 2005;Schierl et al 2009). In this context, most of the recently published studies give particular attention to the assessment of surfaces contamination and report a generalized contamination, even in hospitals with the best equipment and strict safety procedures (Turci et al 2003;Hedmer et al 2005;Mason et al 2005;Brouwers et al 2007;Hon et al 2011Hon et al , 2013Kopp et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This problem is notable because, although there are other routes of exposure, studies have indicated that dermal absorption is the main route of occupational exposure to antineoplastic drugs. [9][10][11][12] To the authors' knowledge, few studies have examined dermal contamination among hospital workers. In a study performed in the Netherlands, Fransman and others 13 found contamination on the hands of pharmacy technicians involved with drug preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation results from aerosolisation of powder or liquid during reconstitution and spillage taking place while preparing or administering to patients; skin contact or skin absorption results from contact with contaminated surfaces mostly when control measures are inadequate. This type of exposure seems to have the most important role in dermal absorption (20,79,90,91).…”
Section: Occupational Exposure To Antineoplastic Drugsmentioning
confidence: 99%